Pengaruh Probiotik Bakteri Asam Laktat dalam Air Minum Terhadap Konversi Pakan Ayam Broiler - Azizah, Nanda Kholifatul; Sarmanu, Sarmanu; Utomo, Budi; Sabdoningrum, Emy Koestanti; Lokapirnasari, Widya Paramitha; Supranianondo, Koesnoto (Universitas Airlangga, 2020)
This study aimed to determine the effect of probiotics of lactic acid bacteria in drinking water on feed consumption, weight gain and feed conversion ratio of broiler chickens. This research is an experimental research. The experimental animals used in this study were 28 male broiler chickens strain Cobb 700 aged 20 days. P0 was not given the addition of probiotic lactic acid bacteria, P1 was given the addition of probiotic lactic acid bacteria Lactobacillus acidophilus in 1ml/liter drinking water, P2 was given the addition of probiotic lactic acid bacteria Lactobacillus casei in drinking water 1ml/liter, P3 was given the addition of probiotic lactic acid bacteria Lactobacillus fermentum in drinking water 1ml/liter, P4 was given the addition of probiotic lactic acid bacteria Lactobacillus plantarum in drinking water 1ml/liter, P5 was given the addition of probiotic lactic acid bacteria Pediococcus in drinking water 1ml/liter, P6 was given the addition of probiotic mix lactic acid bacteria in drinking water 1ml /liter. Collecting data for the last 1 week by weighing the remaining consumption of feed given and weight gain of broiler chickens. The data obtained were analyzed using the Analysis of Variant (ANOVA) statistical method and continued with Duncan. Based on the results of the calculation of the amount of feed consumption and weight gain in broiler chickens, it showed that the administration of probiotic lactic acid bacteria 1ml/liter of water in broiler chickens could increase body weight gain, reduce feed conversion rates but did not reduce broiler feed consumption (p<0.05).